Repository for extended dark matter object constraints - Djuna Croon; Sergio Sevillano Muñoz (European Physical Journal C: Particles and Fields, 2025)
Abstract Extended dark matter objects (EDOs) are popular dark matter candidates that interact gravitationally with the Standard Model. These gravitational interactions can be used to constrain their allowed parameter space. However, EDOs can have different formation mechanisms, sizes, and shapes, requiring a case-by-case analysis when studying their impact on different areas of cosmology. We thus present a repository of all available bounds for these objects, with a code that allows plotting user-defined combinations of all up-to-date bounds for a given shape and different radii. We propose a standard for the EDOs’ mass profiles so that different sets of bounds are consistent with each other, and provide instructions on using the code and contributing to the repository.